1993
DOI: 10.1002/hep.1840180308
|View full text |Cite
|
Sign up to set email alerts
|

Refractory ascites in cirrhosis: Roles of volume expansion and plasma atrial natriuretic factor level elevation

Abstract: Cirrhotic patients with ascites refractory to diuretics also have blunted response to marked elevations of plasma atrial natriuretic factor levels alone or to moderate intravascular volume expansion by head-out water immersion. However, these patients usually undergo natriuresis after peritoneovenous shunting. To dissect the factors responsible for this response, we studied the effects on separate days of moderate intravascular volume expansion and highly elevated plasma atrial natriuretic factor levels (head-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Wong et al. 29 reported that massive (as opposed to moderate) volume expansion or greatly elevated levels of plasma atrial natriuretic factor associated with moderate volume expansion can improve blunted atrial natriuretic factor responsiveness in cirrhotic patients with refractory ascites. Thus, volume expansion could represent a way to improve natriuretic response in patients with refractory ascites.…”
Section: Discussionmentioning
confidence: 99%
“…Wong et al. 29 reported that massive (as opposed to moderate) volume expansion or greatly elevated levels of plasma atrial natriuretic factor associated with moderate volume expansion can improve blunted atrial natriuretic factor responsiveness in cirrhotic patients with refractory ascites. Thus, volume expansion could represent a way to improve natriuretic response in patients with refractory ascites.…”
Section: Discussionmentioning
confidence: 99%
“…All patients fulfilled prevailing criteria for refractory ascites by the International Ascites Club . Prior to 1996, diagnosis of refractory ascites was based on our standardized critieria, which were very similar to those of International Ascites Club. Patients with alcoholic cirrhosis had to abstain from alcohol for ≥ 6 months.…”
Section: Methodsmentioning
confidence: 99%
“…Patients with sodium-retaining disorders are resistant to the effects of ANP infusion or to endogenously released ANP during head-out immersion (28,34,35). It is reasonable to suggest that humans with GC-A deficiency are more vulnerable to volume expansion in such pathological conditions.…”
Section: Figmentioning
confidence: 99%